Kualitas Kertas Seni Dari Pelepah Tanaman Salak Melalui"Biochemical" Jamur Phanerochaete Crysosporium Dan Pleurotus OstreatusDengan Variasi Lama Pemasakan Dalam Naoh - Asfa, Aulia Asifati; , Triastuti Rahayu, M.Si (2016)
Art paper or so-called recycled paper is paper commonly used as materials for handicrafts. Usually it made from crop wastes that contain high fiber. Waste plant frond bark utilized contain high fiber which can be utilized as raw material for paper making art. The raw material is processed through biopulping by fungus Phanerochaete crysosporium and Pleurotus ostreatus. The purpose of this study was to determine the quality of art paper from the midrib of zalacca through biochemical by fungus Phanerochaete crysosporium and Pleurotus ostreatus on variation of ripening duration in NaOH with tensile strength test, power tear and organoleptic test (texture, color, appearance fibers and acceptance of society). This research method used a completely randomized design (CRD) with two factors, one that is ripening duration in NaOH 15% (P1 = 1 hour, P2 = 2 hours) and factor 2 is a incubation duration (L1 = 30 days, L2 = 45 days) with 4 treatment. Result of this research shows that the best quality art paper is P2L1 (ripeningduration time of 2 hours and 30-days incubation) is 0,243 N/mm2 which is an tensile strengt test results and 18.711 N which is the highest tear power, smooth texture, light brown color, appearance of the fibers is less clear and panelists liked to this paper.